Pengaruh Penambahan Gula Terhadap Waktu Fermentasi Sauerkraut Dari Kol (Brassica Oleracea L.) - cynthia perdana putri; Resti Fevria; Moralita Chatri; Afifatul Achyar (Fakultas Tarbiyah dan Ilmu Keguruan, Institut Agama Islam Negeri Kerinci, 2020)
Cabbage (Brassica oleracea L) is a type of vegetable that is widely grown in high altitude areas, and has good benefits for health and can ward off disease. Cabbage is easily wilted, damaged and rotten. Fermentation is a food preservation process, which plays a role in improving the nutritional content, extending the shelf life of food. Fermentation of cabbage with the addition of salt is called sauerkraut. Fresh cabbage fermented into sauerkraut uses salt with a certain concentration, so no need to add other microorganisms as a starter (inoculum) or yeast, because lactic acid bacteria already exist in cabbage. This research is an experimental study carried out in December 2019 until January 2020, at the Biology Research Laboratory, FMIPA UNP. The design used in this study was a complete random design (CRD) with four treatments and five repetitions. In the treatment, 2.5% salt content and 2.5%, 5%, 7.5% and 10% sugar variation were used. The main observational parameters included fermentation time. Data were analyzed using the Analysis of Variance (ANOVA) test and further tested with DNMRT at the 0.05 level. Based on research results found that the addition of sugar in the fermentation process of sauerkraut affects the fermentation time.